Reactions of 2-(Diformylmethylidene)-3,3-dimethylindole with hydrazides: synthesis of new pyrazolylindolenine derivatives-the unprecedented one-pot pyrazole-thiadiazole double annulation - Khaledi, H.; Ng, S.W.; Thomas, N.F.; Ali, Hapipah Mohd (2011)
A series of new pyrazolylindolenine derivatives has been synthesized through the reaction of 2-(diformylmethylidene)-3,3-dimethylindole (diformyl), prepared by the Vilsmeier reaction, with six different hydrazides. Although the reaction of p-toluenesulfonylhydrazide and S-benzyldithiocarbazide with diformyl yielded the expected pyrazolylindolenines as the sole products, the initial products of the reactions of diformyl with semicarbazide, thiosemicarbazide, and carbohydrazide underwent cleavage. The reaction of diformyl with thiocarbohydrazide resulted in a unique one-pot formation of pyrazole and thiadiazole rings, conjugated with the indolenine component. The solid state structures of these heterocycles were established by X-ray crystallographic analysis.